Generational Differences in the Workplace: There Is Complexity Beyond the Stereotypes. Issue 3 (2nd October 2015) - Lyons, Sean; Urick, Michael; Kuron, Lisa; Schweitzer, Linda
Abstract : The topic of generational differences in the workplace has been immensely popular over the past decade, spawning a large number of academic publications and a far greater number of consulting reports, popular press books, magazine articles, media reports, blogs, and infographics. Indeed, a new industry of consultants and public speakers seems to have emerged primarily to capitalize on the popularity of this topic. As Costanza and Finkelstein (2015 ) note, the research on this "hot topic" has often seemed opportunistic, lacking rigor and depth. The relative ease of cutting existing cross-sectional data by age and calling it a generation study has tempted researchers to hop on the bandwagon, resulting in a large number of empirical studies with nearly identical literature reviews that overrely on popular press and opinion-based literature. There has been a lamentable tendency toward blind empiricism with little or no connection to theory, as has been stated elsewhere (Lyons & Kuron, 2014 ; Parry & Urwin, 2011 ).